Optimization Design and Experiment of Soil-Covering Device for Astragalus Mulching Transplanting Machine - Bin Feng; Wei Sun; Shanglong Xin; Guanping Wang; Wenjing Lv; Junzeng Wang (Agriculture)
In response to the low efficiency and poor soil quality of the mechanized transplanting of Astragalus, and in combination with the agronomic requirements of Astragalus mulching and outcrop cultivation, an Astragalus film mulching transplanting machine was designed, which integrates functions such as trenching, seedling feeding, mulching, and seed row soil covering. Firstly, based on the analysis of the overall structure of the transplanting machine, the structure and working principle of the soil-covering device are expounded, and the structure and working parameters of the soil-covering disc and soil-covering drum are clarified. In order to optimize the performance of the soil-covering device of the mulching transplanting machine and improve the quality of the covering soil, the Box–Behnken response surface test design method was adopted. The depth of disc extraction, the disc deflection angle, and the rotation speed of the soil-covering drum were selected as the main influencing factors. The quantity of soil cover and variation coefficient of soil cover quantity uniformity were used as the evaluation indicators for the quality of the operation, and parameter optimization experiments were conducted. By establishing a regression mathematical model between influencing factors and evaluation indicators, analyzing the interactive effects of each factor on response values, and comprehensively optimizing the model, the optimal parameter combination was obtained. The results of field experiments show that when the depth of disc extraction is 95 mm, the disc deviation angle is 40°, and the rotation speed of the soil-covering drum is 30 r/min, the corresponding quantity of soil cover and variation coefficient of soil cover quantity uniformity are 10.61 kg/m and 1.79%, respectively, which can meet the soil covering requirements. The research results can provide technical references for the structural optimization and performance improvement of the soil-covering device of the traditional Chinese medicine mulching transplanting machine.